DETERMINATION OF ANTIMICROBIAL ACTIVITY OF THE DYED SILK FABRICS WITH SOME NATURAL DYES - (:unkn) unknown (My University, 2015)
Bu çalışmada, ipek kumaş doğal indigo bitkisi ile boyanmıştır. Sonra 20x20 cm2 boyutunda kesilmiştir. Bir kumaş hariç tüm kumaşlar aynı yüzdede şap (KAl(SO4)2.12H2O) çözeltisi ile mordanlanmıştır. Yeşil renk boyama için kumaşlar önce ayrı ayrı muhabbet çiçeği (Reseda luteola) ve mazı gomalağı (Quercus inf ectoria Olivier) ile daha sonra iki bitki beraber farklı yüzdelerde kullanılarak boyama yapılmıştır. Antimikrobiyel test 27 adet ipek kumaş için uygulanmıştır. Testler Stap hylococcus aureus ATCC 6538 e karşı yapılmıştır. Sayım sonuçları koyu renkli kumaşlarda S.aureus un daha fazla azaldığını göstermiştir. Canlı mikroorganizma sayısı CFU/ml olarak koloni sayımı ile belirlenmiştir. Bakteri azalması tayin edilmiştir. Boyama yapılmış ipek kumaşlardaki renk bileşenleri ve onların yüzdeleri HPLC-PDA (yüksek performanslı sıvı kromatografisi) ile renk ölçümleri ise CIEL*a*b* spektorofotometresi yardımıyla belirlenmiştir.

In this study, silk fabric is dyed with natural indigo. Dyed silk fabric with natural indigo was cut in the 20x20 cm2 size. Excluding a fabric, all fabrics were mordanted in the same percentage with alum metal (KAl(SO4)2.12H2O). Then, silk fabrics for green color dyeing are dyed separately with weld (Reseda luteola), gall oak (Quercus inf ectoria Olivier) and together weld (Reseda luteola) and gall oak (Quercus inf ectoria) in different percentage. Antimicrobial functionality of the twenty seven silk fabrics is established. Tests were conducted against the Stap hylococcus aureus ATCC 6538. The results of the counting test showed more reduction of survival Stap hylococcus aureus in dark-colored fabric. The number of survival microorganism was determined by counting the colonies as colony-forming unit (CFU/ml) and reduction rate of bacteria was calculated. Coloring compounds and their percentages in the natural dyed silk fabrics are detected by HPLC- PDA (high performance liquid chromatography with diode array detection). Colour measurement is done of the dyed silk fabrics by CIEL*a*b* spectrophotometer.
BAZI DOĞAL BOYALAR KULLANILARAK BOYANMIŞ İPEK KUMAŞLARIN ANTİMİKROBİYAL AKTİVİTESİNİN BELİRLENMESİ